2024
DOI: 10.3390/molecules29071449
|View full text |Cite
|
Sign up to set email alerts
|

Royal Jelly Enhances the Ability of Myoblast C2C12 Cells to Differentiate into Multilineage Cells

Takumi Ito,
Thira Rojasawasthien,
Sachiko Yamashita Takeuchi
et al.

Abstract: Royal jelly (RJ) is recognized as beneficial to mammalian health. Multilineage differentiation potential is an important property of mesenchymal stem cells (MSCs). C2C12 cells have an innate ability to differentiate into myogenic cells. Like MSCs, C2C12 cells can also differentiate into osteoblast- and adipocyte-lineage cells. We recently reported that RJ enhances the myogenic differentiation of C2C12 cells. However, the effect of RJ on osteoblast or adipocyte differentiation is still unknown. Here in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Bouamama et al (124) demonstrated some mechanisms that delay PBMCs' cell senescence in vitro by RJ through enhancing their cell proliferating ability, MDA, GSH, IL-2, IL-6, IL-4 cytokines, and NO release. The immuno-enhancing potential and anti-immunosenescence effects of royal jelly may play a primordial role in the health of the elderly to corroborate and combat pathological aging by improving the immune functions, enhancing PBMCs' proliferation along with the cytokine release [123][124][125].…”
Section: Cellular Senescence Chronic Inflammation: Age-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouamama et al (124) demonstrated some mechanisms that delay PBMCs' cell senescence in vitro by RJ through enhancing their cell proliferating ability, MDA, GSH, IL-2, IL-6, IL-4 cytokines, and NO release. The immuno-enhancing potential and anti-immunosenescence effects of royal jelly may play a primordial role in the health of the elderly to corroborate and combat pathological aging by improving the immune functions, enhancing PBMCs' proliferation along with the cytokine release [123][124][125].…”
Section: Cellular Senescence Chronic Inflammation: Age-related Diseasesmentioning
confidence: 99%
“…Increase in overall well-being and recuperation from fatigue and menopausal problems [90,121,202,211,223,224] Against stenocardia and after heart attack; arteriosclerosis and atherosclerosis; hypertension [187,188,190,195,197,[202][203][204] Against respiratory system diseases, asthma [333,338,339] Against diseases the eye, e.g., blepharitis, conjunctivitis and retina burns, circulatory disorders in the eye [97,126,161] Bio-stimulating effect, increases physical endurance and work ability and increases resistance to hypoxia [52,124,125,152] Increase memory, neuro-vegetative activation [137,138,141,145,147,154,157 RJ has been used for a long time. The first recommendation for its use in human therapy dates from 1922 in France.…”
Section: Usage References Pediatricsmentioning
confidence: 99%